Atenção à saúde da criança quilombola menor de 2 anos: saberes e práticas de cuidado à luz da teoria transcultural - Melo, Letícia Oliveira de (2016)
The early years of a child's life, especially the first two, are characterized by accelerated growth and significant acquisitions in the development process. The priority in the health care of the child of 0-2 years is recognized by the Ministry of Health with the proposal to protect and foster the integral development of the child in this critical and sensitive period of early childhood. Thus, it is fundamental to investigate how care of children occurs in the family environment, since the family is the first social institution that, together with others, seeks to ensure the continuity and well-being of its members and the community, including protection and The well-being of the child. The objective was to analyze the knowledge and practices of family care in the health care of the quilombola child under 2 years in light of the Leininger Transcultural Theory. Qualitative research, supported by Ethnonursing and the theoretical framework of the Theory of Diversity and Universality of Care of Madeleine Leininger, held in the Quilombola community of Muquém, in the municipality of União dos Palmares-AL. Participants were the main caregivers of children under 2 years of age in this community, totaling sixteen, codenames were used in honor of personalities who were part of the history of the Brazilian quilombola culture in order to preserve their identity. The data collection took place from April to July 2016 in a locus with immersion of the researchers in the field following the four phases of observation, participation and reflection proposed by Leininger. The instruments used in the collection were: field diary, socio-demographic form, observation guide and semi-structured interview, which were recorded. The research was approved by Plataforma Brasil with n ° 1,500,684. The analysis was organized according to the four phases of Leininger's ethnonursing. The first two include recording all data and encoding. The third phase requires the researcher to identify recurrent patterns and the fourth phase the themes. The results were structured in three themes: 1. Knowing the participants of the study 2. Knowledge and practices popular in the daily care of quilombola children; 3. Knowledge and popular practices of care in sickness situations. In the category of Knowledge and Popular Practices in Daily Quilombola Care, the daily care of children from zero to two years of age is predominantly performed by the women of this community. According to the caregivers, the care with hygiene, food and prevention are influenced by the beliefs, customs and rites that are passed on from generation to generation. In the category Knowledge and popular practices of care in situations of illness, it was verified that in these situations the family initially cares for the home, counting on the support network made up of family and friends. These practices are mainly based on the use of medicinal plants and religious practices that are carried out by healers of the community itself. It is concluded that the transcultural theory allows the opportunity to re-signify nursing practice, combining scientific knowledge with popular knowledge.